Modelling, Simulation And Control Of A Series Hybrid Electric Vehicle - Rahmat, Mohd Sabirin (2015)
Series hybrid electric vehicles (SHEVs) are efficiently used in many cities to reduce harmful exhaust emissions, as well as, fuel consumption. The vehicles are propelled with an electric motor that can achieve high efficiency at low speed with an internal combustion engine being operated at optimum fuel consumption for battery charging. Human interaction is being increasingly used to assist the development propulsion systems for road vehicles. The modelling of the hybrid electric powertrain for mobility is indeed challenging. The model should not only adequately simulate the vehicle longitudinal dynamics, it should also account for the load control of the propulsion system. The aims of this study are to design a control strategy for an electric motor of a SHEV longitudinal model and to assess its mobility performance. A mathematical model, for a vehicle with an internal combustion engine, was set-up to simulate its longitudinal dynamics using a high-level programming language software; i.e. Matlab Simulink. The multibody system approach was employed to model the vehicle dynamics with six degree of freedoms. Cases to investigate the inertia performance, such as sudden acceleration and braking, were conducted. The model was verified using a commercial vehicle simulation software; i.e. Car Simulation for Education (CarSimEd). The finding suggests that the model works as desired and was verified by CarSimEd. The SHEV propulsion system utilises a PMSM model to provide a driving effort to propel the vehicle. The SHEV operates at high efficiency when the model had applied a control strategy for the PMSM model to track a desired torque. The gain scheduling controller was selected for the motor due to its effectiveness provide a drive torque in various driving conditions. The performance for the control strategy was tested using the sine, square, sawtooth and step inputs. The results indicate that the controller for motor control is sufficiently efficient to track various types of the desired inputs. The SHEV was set up by integrating the vehicle longitudinal model and the electric motor model. Longitudinal tests were performed; i.e. sudden acceleration and braking, tracking road gradient and unbounded motion. The findings suggest that the SHEV model is suitable for use in the preliminary assessment for other types of HEVs or EVs. Simulations using the CarSimEd show similar results.